Requirements engineering issues and challenges in Ukrainian Agile-projects (Моделювання, керування та інформаційні технології, 2023)
In this paper, a review of scholarly studies related to the issues of requirements engineering in Agile as well as a survey study in the Ukrainian IT community, are carried out. This paper aims to adjust the research done on this issue, to identify the current challenges of requirements engineering in Agile and their impact on the final production. Based on the results of the analysis, further research steps are planned. This paper is a preparation for the search for a technical solution to the identified issues and challenges and contributes to the theoretical knowledge of requirements engineering problems in Agile.